1981
DOI: 10.2307/1589923
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Chickens to Avian Nephritis Virus at Various Inoculation Routes and Ages

Abstract: Factors that influence the response of chickens to avian nephritis virus (ANV) were studied. Day-old specific-pathogen-free chicks were inoculated with the G-4260 strain of ANV by oral, subcutaneous, intratracheal, intramuscular, and intracerebral routes at a dose of 10(5.0) plaque-forming units (PFUs) per chick. Inoculation induced only nephritis, and contact infection ANV occurred very easily. When 1-, 14-, 28-, 56-, and 300-day-old chickens were inoculated orally with 10(5.0) PFUs of the virus, the day-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 3 publications
0
17
1
2
Order By: Relevance
“…Many studies have shown that the pathogenicity of ANV-1 is limited to the kidney of chickens, in contrast to the damage observed in the kidney, pancreas, duodenum, thymus, bursa and liver that was seen after infection with isolate 19 (Imada, 2008). This pathogenicity of isolate 19 was observed after infection of 3-week-old SPF layers, whereas several strains of ANV-1 caused considerable mortality in 1-day-old SPF chicks but not in older birds (Imada et al, 1981;Frazier et al, 1990;Narita et al, 1990;Shirai et al, 1991aShirai et al, , b, 1992Reece et al, 1992). These differences can be explained by the different type of ANV strains, by strain of bird, route of inoculation or level of maternally derived antibodies; other experimental conditions should also be taken into account (Mandoki et al, 2006;Reynolds & Schultz-Cherry, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have shown that the pathogenicity of ANV-1 is limited to the kidney of chickens, in contrast to the damage observed in the kidney, pancreas, duodenum, thymus, bursa and liver that was seen after infection with isolate 19 (Imada, 2008). This pathogenicity of isolate 19 was observed after infection of 3-week-old SPF layers, whereas several strains of ANV-1 caused considerable mortality in 1-day-old SPF chicks but not in older birds (Imada et al, 1981;Frazier et al, 1990;Narita et al, 1990;Shirai et al, 1991aShirai et al, , b, 1992Reece et al, 1992). These differences can be explained by the different type of ANV strains, by strain of bird, route of inoculation or level of maternally derived antibodies; other experimental conditions should also be taken into account (Mandoki et al, 2006;Reynolds & Schultz-Cherry, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…On this basis, we can speculate that very young (1 to 4 days) chicks will be more severely affected by substantial ANV challenges than older (7 days and older) chicks. Earlier studies have shown that experimental ANV infections of specific pathogen free chicks were more pathogenic following infection at 1 day old than infection at 14 days old (Imada et al, 1981). In the field situation, the appearance of clinical signs such as diarrhoea, depressed condition and even growth arrest as early as 6 to 7 days in flocks that go on to develop severe stunting problems, suggest that the chicks have received a severe infectious challenge before this time.…”
Section: Discussionmentioning
confidence: 99%
“…ANV typically causes histological changes in the kidneys (Shirai et al, 1989(Shirai et al, , 1991b(Shirai et al, , 1992Jordan & Pattison, 1996), although viral antigens can be detected in the liver, spleen, pancreas, kidney, jejunum, and rectum (Imada et al, , 1983. Young chicks are the most susceptible, with resistance to disease developing after the first month of life (Imada et al, 1981). Antibodies against ANV have been found in chicken and turkey flocks throughout the UK and Japan, suggesting a broad distribution (Nicholas et al, 1988;Takase et al, 2000).…”
Section: Avian Nephritis Virusmentioning
confidence: 99%
“…TAstV can also be isolated in embryonated eggs, although no tools to detect the presence of antibodies against TAstV-1 or TAstV-2 have been described (Reynolds, 1991;Koci et al, 2000b). Furthermore, ANV is the only AAstV shown to replicate in cell culture (Imada et al, 1981).…”
Section: Diagnosismentioning
confidence: 99%